2017
DOI: 10.1080/14764172.2017.1288259
|View full text |Cite
|
Sign up to set email alerts
|

Soybean-fragmented proteoglycans against skin aging

Abstract: A beneficial effect of the Proteum serum was demonstrated with an improvement in the skin roughness and a reinforcement of the skin barrier function. Moreover, a significant protector effect on human stratum corneum against lipids peroxides (LPO) was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Earlier published reports suggest that proteoglycan synthesis can be stimulated by the application of certain topical peptides (such as copper peptide and carnosine), 18 but to our knowledge, the effects of the particular peptide in the tested product (tetradecyl aminobutyroylvalylaminobutyric urea trifluoroacetate) have not been published. Barba et al 19 have reported the effects of a serum containing fragmented proteoglycans from soybeans on collagen and proteoglycan levels in vitro, although their results are not directly comparable to ours due to differences in methodology. Our study was a comparison of aged and serum-treated skin against aged untreated skin and nonaged skin, and we found that levels in serum-treated samples were close to those of healthy, nonaged skin.…”
Section: Discussioncontrasting
confidence: 84%
“…Earlier published reports suggest that proteoglycan synthesis can be stimulated by the application of certain topical peptides (such as copper peptide and carnosine), 18 but to our knowledge, the effects of the particular peptide in the tested product (tetradecyl aminobutyroylvalylaminobutyric urea trifluoroacetate) have not been published. Barba et al 19 have reported the effects of a serum containing fragmented proteoglycans from soybeans on collagen and proteoglycan levels in vitro, although their results are not directly comparable to ours due to differences in methodology. Our study was a comparison of aged and serum-treated skin against aged untreated skin and nonaged skin, and we found that levels in serum-treated samples were close to those of healthy, nonaged skin.…”
Section: Discussioncontrasting
confidence: 84%
“…Skin aging results in a thinner and less well‐protected skin 13,14 . It is caused by a combination of genetic factors and exposome factors (environmental and biological factors) on top of chronological aging 15 .…”
Section: Discussionmentioning
confidence: 99%
“…They are composed of amino acids, and they can imitate peptide sequences or act as messenger molecules stimulating the production of collagen, elastin, and lumican rebuilding the dermal matrix, reducing the appearance of wrinkles and to increase firmness 21–24 . Collagen (COL) is the major ECM molecule in the dermis, along with other components that confer properties on the skin 14 25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations